If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -32 = -6(3s + 9) Reorder the terms: -32 = -6(9 + 3s) -32 = (9 * -6 + 3s * -6) -32 = (-54 + -18s) Solving -32 = -54 + -18s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '18s' to each side of the equation. -32 + 18s = -54 + -18s + 18s Combine like terms: -18s + 18s = 0 -32 + 18s = -54 + 0 -32 + 18s = -54 Add '32' to each side of the equation. -32 + 32 + 18s = -54 + 32 Combine like terms: -32 + 32 = 0 0 + 18s = -54 + 32 18s = -54 + 32 Combine like terms: -54 + 32 = -22 18s = -22 Divide each side by '18'. s = -1.222222222 Simplifying s = -1.222222222
| 4.2=a+6.4+1.1 | | -16x^2+143x+9=0 | | 13x-20=5x+36 | | x^2+50x+464=0 | | 1n+2n=6 | | -16x^2+143t+9=0 | | 1n+2n=5 | | -4-7k=-12-6k | | (-26)+31= | | 328=x-31+219 | | -0.18x+y=-6.54 | | n^2-n+2.5=200 | | 6r-2r+6r=r | | -13=1+7v+7v | | 13=5(1+2n)-4(n-4) | | -481=-15j-61 | | -3n+8n=21 | | -4n+3n=2 | | 4x+2x-7=41 | | 5x+5y=4y-7 | | 2x-6-4x=8 | | 5x-9+2x=3+7x-12 | | 5x-23=3x-11 | | 3z-7-2=0 | | b+6-2b=14 | | -x-2(9-8x)=13 | | 0=(9-x)(11-2x) | | 2-n=2 | | .3x-.4x-1=3 | | 8x^3-12x^2-8x+1=0 | | -14+6b+7-2v=1+5b | | y=-3y+6 |